Interprofessional Education in Health Informatics (IPEHI) for Health Sciences Programs - Alanazi, Abdullah (Advances in medical education and practice, 2023)
Background: Given the significant changes the healthcare system has undergone recently; information technology has become an indispensable tool. To properly train future healthcare providers, it is vital to introduce information technology courses in Health Sciences programs. The provision of healthcare services now requires teamwork, which has led to the need for interprofessional education in health sciences schools. Therefore, this study explores the necessity of introducing Interprofessional Education in Health Informatics (IPEHI) in health sciences programs. Additionally, the structure and content of the course were assessed. Methods: A mixed-method approach was employed in this study to explore the need for health informatics interprofessional education among individuals with a health-related science background and who possessed health informatics expertise through work experience or formal post-graduation education. Following a cross-sectional survey-based study, expert subjects from academia and the workplace were convened for Delphi meetings to create an IPEHI course founded on the CAHIIM competency framework. Results: 128 questionnaires were collected from three cities in Saudi Arabia. Of all the respondents, 80% agreed that the present health sciences education should be expanded. Additionally, 74% of them agreed that the proposed IPE-HI (Interprofessional Education in Health Informatics) would enhance their knowledge and positively impact the healthcare system. During the second phase, eight experts were invited to identify seven domains, which include health information science and technology, social, behavioral and information science and technology applied to health, information science and technology, leadership, social and behavioral aspects of health, professionalism, and interprofessional collaborative practice. The results emphasize the need for introducing an IPE-HI, as previous studies have also shown that educating health professionals in health information technology is crucial. Conclusion: IPEHI plays a crucial role in producing competent health science graduates. Consequently, experts have developed and validated a proposed IPE-HI course. Keywords: interprofessional education, health informatics, health education